A Literary Study on Vermilionum - Ki-Rok Kwon; Tae-Sik Kang; Sung-wook Kim (Korean Pharmacopuncture Institute, 2003)
Results 1. Vermilionum is made from the mixture of mercury and sulfur, resulting in reddish mercuric sulfide(Hg2S). 2. The characteristics for Vermilionum are pungent and sweet, has warm temperature, and enters heart, lung, and stomach meridians. 3. The efficacies of Vermilionum are to eliminate parasites, expels phlegm and dampness, and sedate heart and calm spirit. 4. Long-term intake make results in mercuric toxication. 5. Further researches on the administration methods and dosages are required to reduce side effects.